Structured pharmaceutical care improves the health-related quality of life of patients with asthma. Issue 1 (December 2017) - Anum, Philip; Anto, Berko; Forson, Audrey
Abstract Background Asthma as a chronic health condition can be controlled when in addition to clinical care, adequate education and support is provided to enhance self-management. Like many other chronic health conditions improved self-management positively impacts the health-related quality of life (HRQoL). It can therefore be said that a well-structured pharmaceutical care delivery that addresses the issues related to patient education and support towards self-management stands a good chance of positively impacting asthma control. This study evaluated the impact of a structured pharmaceutical care delivery on asthma control. Methods A prospective pre-/post- intervention study of a single cohort of 77 adult out-patients visiting specialist asthma clinics in Ghana were assessed for HRQoL and peak expiratory flow rates (PEFR) one month after pharmaceutical care intervention. Pharmaceutical care intervention covered education on the health condition, pharmacotherapy and self-management issues as well as correction of inhaler-use technique, where necessary and when to urgently seek medical care. The mean difference of the HRQoL and PEFR values were subjected to paired samplest -test analysis. Results Delivery of a structured pharmaceutical care led to a significant improvement in asthma specific quality of life and PEFR. The mean paired difference of the HRQoL for a cohort of patients with asthma post- pharmaceutical care intervention was 0.697(95% CI: 0.490 - 0.900) att = 6.85 (p < 0.05). The mean paired difference for PEFR post intervention was 17.533 (95% CI: 2.876 - 32.190) att = 2.384 (p = 0.02). Conclusion This study identified important challenges with both the pharmacologic and the non-pharmacologic management of adult asthma patients. Inadequate inhaler-use skills, widespread occurrence of preventable adverse events and irregular use of preventer medicines were prevalent among patients. At one month after pharmaceutical care intervention, patients with asthma in a cohort follow-up study showed significant improvements with regard to asthma-specific quality of life, peak flow rates and knowledge Trial registration GHS-ERC : 08/9/11 of October 19, 2011.